The use of passive voice in newspaper reports - Šebková, Kateřina (Univerzita Pardubice, 2009)
The bachelor work focuses on the use of individual types of passive voice in discourse of quality British press. Theoretical part characterizes basic features of newspaper report style, generally describes the active and passive voice and functions of passives with regard to the analytical character of English. The analytical part examines the frequency of occurrence of passives as well as its function in newspaper discourse. The attempt is to prove and describe the influence of news discourse to the incidence of long and short passives.
Užití pasiva v článcích novinových zpráv
Keywords: trpný rod; dlouhé pasivum; krátké pasivum; konatel; kontext; aktuální členění větné; passive voice; long passives; short passives; Agent; context; functional sentence perspective